2016
DOI: 10.1051/parasite/2016059
|View full text |Cite
|
Sign up to set email alerts
|

A targeted door-to-door strategy for sleeping sickness detection in low-prevalence settings in Côte d’Ivoire

Abstract: Significant efforts to control human African trypanosomiasis (HAT) over the three past decades have resulted in drastic reductions of disease prevalence in Côte d’Ivoire. In this context, the costly and labor-intensive active mass screening strategy is no longer efficient. In addition to a more cost-effective passive surveillance system being implemented in this low-prevalence context, our aim was to develop an alternative targeted active screening strategy. In 2012, we carried out a targeted door-to-door (TDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Subsequently, a large portion of the literature is concerned with how best to deploy existing tools in support of elimination goals. In this respect, a lot of attention was assigned to screening approaches [43,44,[70][71][72][73][74][75][76][77] and exploring testing algorithms [50,55].…”
Section: Goal: Global Eliminationmentioning
confidence: 99%
“…Subsequently, a large portion of the literature is concerned with how best to deploy existing tools in support of elimination goals. In this respect, a lot of attention was assigned to screening approaches [43,44,[70][71][72][73][74][75][76][77] and exploring testing algorithms [50,55].…”
Section: Goal: Global Eliminationmentioning
confidence: 99%
“…Therefore, the efficacy of active screening campaigns may be improved by reducing systematic nonparticipation, potentially by mini teams who screen from house-to-house rather than in the village center. A door-to-door mobile screening strategy in Côte d’Ivoire was found to detect significantly more HAT cases than standard active screening [ 11 ]. Previous modeling studies have shown that targeted screening, resulting in increased coverage of high-risk groups, could lead to a greater chance of HAT elimination in some high-endemicity settings [ 5 , 6 ].…”
Section: Targeted Active Screeningmentioning
confidence: 99%
“…The last epidemic was contained in the Sinfra and Bonon foci at the early2000s [ 6 – 8 ]. Despite continuous control efforts, few HAT cases are still passively diagnosed from these two foci as well as from historical foci of the Western-Centre part of the country [ 7 9 ]. Transmission persistence may be due to the existence of a residual chronic human and/or animal reservoir of T .…”
Section: Introductionmentioning
confidence: 99%